Characteristics of an effective teacher for the gifted - Peñaflor, Carmen R. 1942- (College of Education, University of the Philippines Diliman, 1968)
The study discussed the characteristics of an effective teacher for the gifted. As a person, the teacher for the gifted should possess superior intellectual and personal qualities. As a manipulator of the pupil's environment, he needs to have general and special learning and teaching skills. It is hoped that knowledge of these characteristics may help provide some guidance in selecting, preparing, and training our teachers for the education of the gifted. The writer explored periodicals, books, and yearbooks, to gather data regarding personal qualifications of effective teachers for the gifted and the necessary educational preparation he must have.